EFFECTS OF LEADERSHIP STRATEGY ON PERFORMANCE OF GOVERNMENT SECURITY AGENCY (A CASE OF NATIONAL POLICE SERVICE COMMISSION OF KENYA) - Aludo, David Onyango; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
The purpose of this study was to establish the effects of leadership strategy on performance of government security agency and targeted the National Police Service Commission of Kenya as an area of study. Specifically, the study explores the effects of democratic leadership, transformational leadership, transactional leadership and authoritarian leadership on performance of the National Police Service Commission. The effects of leadership strategy and performance of government security agency has been the area of concern and there was need to explore the gaps, which exist between the two areas. The study reviews related literature, which supported the study gaps and necessitated the need for this study. This study used a descriptive research based on the perceptions of senior managers and the operational members of staff, who were used as the respondents of this study. A structured self-completed research questionnaire was administered by hand and collected after a period of two weeks. The component of analysis for this study was 150 employees, which formed the target population for this study. A stratified sampling technique was employed on various categories where 30% of the target population was selected to form the sample size of this study. The response rate of 93.3% from the respondents made it easier for the study to be carried out. Data collected was presented and analyzed using both descriptive and inferential statistics. The statistical package for social science was used to facilitate the data analysis. The study used correlation statistical analysis techniques to aid in establishing the relationship between independent variables and dependent variable. Analysis of variance, means, standard deviation, percentages, graphs and regression model were, used to ease the study findings and discussions. From the study findings, the statistics showed that there was a correlation of democratic leadership and performance with a correlation figure of 0.047, transformation leadership and performance with a correlation figure of 0.089, transactional leadership and performance with a correlation figure of 0.023 and authoritarian leadership and performance with a correlation figure of 0.103. The conclusion of this study showed that the use of democratic leadership and transformational leadership was not fully embraced within the organization, transactional leadership was disputed by the respondents who indicated that its use in the organization may cause high staff turnover and that authoritarian leadership affects efficiency and effective performance negatively. From the conclusions of the study, the study recommended that the organization should embrace democratic leadership but more emphasis should be given transformation leadership. Care should be taken when transactional leadership is to be practiced since it has its short falls and authoritarian should be used as the last resort and needs to be discouraged if efficiency and effective performance is to be realized within the organization.